NUTRITIONAL, SENSORY AND STORAGE PROPERTIES OF SNACK PRODUCED FROM MAIZE (ZEA MAYS LINN) AND AFRICAN YAM BEAN SEED (SPHENOSTYLISSTENOCARPAHOCHST EX A. RICH) FLOUR BLENDS (2014)
Low nutritional value and inconsistent sensory qualities arising from crude and non-standardised processing operations characterise most Nigerian maize-based snacks including kokoro. African Yam Bean Seed (AYB) is an underutilised crop with high nutritional value, but literature is sparse on its utilisation to enrich maize snacks. This study was designed to improve nutritional valueof kokoro by incorporating AYB Flour (AYBF). Varieties of maize (BR-9928-DMR-SY and TZL-Comp-4C2) and AYB (Tss-9 and Tss-30) were tested for processing suitability using physical and chemical properties. The better quality maize and easier to dehull AYB were processed into flours at ratios 100:0, 80:20, 70:30, 60:40 and 0:100. Proximate composition, Trypsin Inhibition Activity (TIA), beta-carotene and amylose contents, functional and pasting properties of the flour blends were determined by standard methods. Using Response Surface Methodology (RSM) experimental design, batters produced from blends of maize and AYBF at ratios 80:20, 70:30 and 60:40 were deep fried at varied temperatures (150, 160 and 170oC) and time (8, 10 and 12 min.) according to 17 combinations associated with three independent variables. Processing conditions including frying temperature, frying time and quantity of AYBF in the flour blends were independent variables while products' qualities were dependent variables. Proximate composition, TIA and texture of snacks were determined using AOAC methods. Kokorowith highest products' qualities were obtained from RSM as the optimum processing conditions. Kokoro was prepared at these optimum conditions and subjected to rancidity test weekly for fourteen weeks to determine its storage life using free fatty acid test. The kokoroand casein diet were separately fed to male wistar rats (90-110g) for 28 days using casein diet as standard to determine its protein availability. Sensory attributes of the products were determined using semi-trained panelists. Data were analysed using ANOVA at p=0.05. The BR-9928-DMR-SY maize was selected for its higher nutrient density (beta-carotene, 1.8μg/g). The AYB (Tss-30) was chosen based on its better ease of dehulling. Crude protein (10.5-15.7%), total ash (1.5-2.2%), crude fibre (1.3-4.1%), sugar (4.1-5.3%), TIA (2.9-6.7%) increased, while crude fat (4.9-3.9%), starch (66.6-51.2%), amylose (26.5-24.8%) and beta-carotene (1.8-0.9μg/g) decreased with increase in AYBF in the flour blends. Functional parameters showed no significant change among the flour blends except oil absorption capacity (80.1-57.1%). Peak viscosity (479-580cp) increased but pasting temperature (89.8-82.1oC) decreased with increase in AYBF. While crude protein content was not adversely affected with higher frying temperature and time, TIA (6.7-2.9%) decreased significantly, but crude fibre, crude fat, sugar and starch contents increased. Texture increased with increase in frying time. The best product was obtained from blend of Maize-AYB at ratio 70:30, fried at temperature, 155oC and time, 11.5min. Level of rancidity of the snack was tolerable up to 12 weeks. Protein availability of the kokorowas not significantly different (p<0.05) from that of casein. The kokoroproduced was acceptable to panelists up to 10 weeks of storage. Addition of African yam bean seed flour to kokoroimproved its nutritional content, creating a novel use for African yam bean seed. Standard processing conditions for producing kokoroof consistent sensory qualities was established.